Approaching E-learning Grid: Applying Grid Computing in e-learning - Dao, Van Tuyet; Ngo, Anh Tuan (Journal of Technical Education Science, 2009)
E-learning has been a topic of increasing interest in recent years. At present, E-learning is being attached special importance as an indeed demand. It helps the lecture to scheduling flexibility as well as supports many tools can now be offered at a widely affordable level. As a result, many E-learning platforms and systems have been developed and commercialized. However, these are based on Client-Server; Peer-to-Peer, or,more recently, Web service architectures, with a major drawback being their limitations in scalability, availability, and distribution of computing power as well as storage capabilities. This paper tries to remedy this situation by proposing the use of Grid Computing - a fairly new powerful technology and will be deployed forthcoming in Vietnam - in the context of E-learning. This is the new environment, which is integrated advantageously the Elearning system into. This paper concentrates on the E-learning system; the base architecture of Grid system and the Grid system’s components. In particular, it is shown what advantages a utilization of Grid computing may have to offer and which application could benefit from it. Moreover, an architect for an E-learning Grid is outlined, and the notion of a Grid Learning object is introduced.